Effect of Short-term Preoperative Dutasteride on Bleeding after Transurethral Resection of the Prostate - Karki, Anup; Shrestha, Naresh Man; Khaniya, Sushil; Subedi, Ratan (Journal of Nepalgunj Medical College, 2025)
Introduction: Transurethral resection of the prostate is the gold-standard surgical treatment for moderate to severe lower urinary tract symptoms due to benign prostatic hyperplasia unresponsive to medical therapy. Bleeding is the most frequent postoperative complication, leading to clot retention, prolonged hospitalization, and increased morbidity. Dutasteride, a 5-alpha-reductase inhibitor, reduces dihydrotestosterone levels, suppresses Vascular Endothelial Growth Factor expression, and decreases prostate vascularity, thereby potentially reducing perioperative bleeding.Aims: To evaluate the effect of 2-weeks preoperative dutasteride therapy on bleeding during TURP.Methods: This prospective interventional study was conducted at Nepalgunj Medical College from September to November 2025. Fifty patients were divided into two groups: Group A received dutasteride 0.5 mg/day for two weeks before Transurethral resection of the prostate, and Group B underwent surgery without dutasteride. All patients underwent standard preoperative evaluations and surgery was performed using a uniform technique by blinded surgeons. Postoperative outcomes were assessed based on hemoglobin and hematocrit changes, clot retention, and hospital stay.Results: Baseline characteristics were similar between groups. Group A showed significantly less postoperative drop in Hemoglobin (0.66 ± 0.55 g/dl vs 1.12 ± 0.72 g/dl; P=0.016) and Hematocrit(4.53 ± 3.09% vs 8.75 ± 2.02%; P=0.02). No patients in Group A developed clot retention, whereas two cases in Group B needed clot evacuation. Hospital stay was significantly shorter in Group A (2.28 ± 0.54 vs 3.08 ± 0.91 days; P=0.000).Conclusion: Short-term preoperative dutasteride therapy significantly reduces bleeding during Transurethral resection of the prostate and shortens hospital stay